Reconstruction Of Lower Lip Avulsion Due To A Human Bite: A Case Report - Gellen, Paula Vitória Bido; de Assis, Lorraine Caroline; Scartezzini, Guilherme Romano; Tavares, Thiago; Brasil, Richard Presley Silva Lima (Seven Editora, 2023)
Lips constitute a fundamental role in facial apparatus as they are responsible for ensuring functional movements besides contributing for phonation, deglutition or swallowing, oral sealing and aesthetics. Lips have a complex anatomy, constituted mainly by the circular muscle of the mouth, besides epithelial layers and mucosa. Avulsions associated with these structures represent real challenges concerning reconstruction complexity and high-risk necrosis. Under this perspective it is fundamental that the planning is efficient in order to provide function and aesthetic back to the patient. Therefore, the current case aims at reporting lower lip reconstruction due to traumatic avulsion as a consequence of human bite in female patients. The initial approach involved a repositioning and fixing of the fragment with suture. However, that attempt failed, which ended up in necrosis of the avulsed stump. As a result, the therapeutic approach was carried on with necrosectomy and labial reconstruction by using axial peninsular composite flaps made by using advancement technique. The one-year post-surgery follow-up presented appropriate aspects, with efficient lip sealing, functional return, absence of necrosis, and guaranteed satisfactory result to the patient. DOI: https://doi.org/10.56238/colleinternhealthscienv1-121